Penerapan blended learning berbasis student centered learning pada mata kuliah matematika ekonomika bagi generasi Z - Mustika Noor Mifrahi (Universitas Islam Indonesia, 2020)
The aim of this study is to analyse the impact of blended learning applied in mathematics economics courses for students in higher education. The Blended Learning method requires students to be actively involved in groups to understand the material and complete the assignment. This study uses two approaches, observation and student perception questionnaire. The objects in this study is student of Study Program of Economics students that taking Mathematics fo Economics subject in academic year 2018/201. The learning methods developed in this program is combination of face-to-face lectures, the provision of instructional videos and the introduction of task completion online sites. The results of measuring the achievements of the program's success indicators are the ability of students to understand and correlate assignments, quizzes and competency tests with a final score of more than 60 or get C as 67%. For each learning objective (LO), the level of learning achievement of LO 1, LO 2 and LO 3 is 70.95%, 46% and 47% respectively. The results of the questionnaire to students showed 60% of students were helped by blended learning system. Based on the results achieved, the proposed learning method can be continued for the next period, but a review of the curriculum, course learning outcomes and the provision of more systematic learning videos are needed.